The effects of multisensory method and cognitive skills training on perceptual performance and reading ability among dyslexic students in Tehran-Iran - Nourbakhsh, Seyed Morteza; Mansor, Mariani; Baba, Maznah; Madon, Zainal (Canadian Center of Science and Education, 2013)
The purpose of this research is to examine the effects of cognitive (cognitive skills training) and developmental intervention (sensory-perceptual skills training) on performance and reading ability of dyslexic students. In the study 60 dyslexic students participated and they were divided into three experimental groups including 20 students as the first experimental group (E1), 20 students as the second experimental group (E2), and 20 students as the control group (C). The effectiveness of the 16-session intervention for both E1 and E2 groups was measured by Reading and Dyslexic test (RTD) as screening test at the beginning and followed by the Bender Visual Motor Gestalt Test (BVMGT) and Rey-Osterrieth Complex Figure test (ROCF). The results were analyzed by using analysis of variance (ANOVA) to compare mean scores among the three dyslexic groups after intervention. Findings suggest that developmental intervention significantly improves RDT, BVMGT and memory scale of ROCF performance of dyslexic students. However, cognitive intervention does not appear to significantly increase performance of the students compared to the control group.